Menakar arah kebijakan Kesejahteraan Sosial Melalui Program Asistensi Rehabilitasi Sosial (ATENSI) Bidang Lanjut Usia - Prayoga, Puspitasari Nurul Darojati; Universitas Binawan Jakarta, (UI Scholars Hub, 2022)
The elderly is the final stage in the human life cycle which is marked by a decrease in functional capability and balance of physiological functions. Problems experienced by the elderly in general are decreased cognitive function, decreased functional ability, namely self-care and instrumental dependence, disability, violence, depression, dementia, self-concept disorders, loneliness, poverty, and neglect. In addition, other problems experienced by the elderly are acts of violence, exploitation, and legal problems. The range of 2020-2021 is the starting point for the development of social welfare policies, especially social rehabilitation programs for the elderly, which is a national priority with a target of 60,000 elderly people. This is a challenge in itself in handling the elderly by using various contemporary approaches, one of which is through the Social Rehabilitation Assistance (ATENSI) program. The present attention for the elderly is carried out with a more comprehensive scheme to fulfill basic needs and rights, carry out their duties and social roles with their families and be able to overcome life's problems. The method chosen by the author in this study is the Study Literature Review related to the Direction of Social Welfare Policy through the ATENSI Elderly Program in Indonesia. The results were obtained. The direction of the ATENSI LU policy is to guarantee the basic rights of those who need services, strengthen an integrated social rehabilitation system, the principles of holistic services, responsive service centers/loka, acceleration of human resources for superior social workers, the important role of involvement and accreditation of Social Welfare Institutions Elderly